Craniofacial morphometric evaluation of Bangladeshi adults by lateral cephalometry with Tweed-Merrifield analysis (Update Dental College Journal, 2014)
Objectives: Craniofacial variations presents in different ethnic populations around the world. Therefore proper morphpmetric comparison of this craniofacial structure with that ethnic norm require to determine dentofacial deformity while orthodontic management. Methodology: To evaluate a morphometric norm of Bangladeshi populations by Tweeds methods of lateral cephalometric parameter, 112 cephalographs of Bangladeshi young adults (56 male, 56 female) with mean age of 19(±2.13) years were traced and evaluated by tweeds analysis on angular measurement. Results: The study shows increase value of FMA with decrease value of IMPA, which indicate that this populations mid-facial height are a bit larger and incisor are a bit retrocline. Conclusions: Differentiation between the Bangladeshi populations value with that of tweeds study explain the craniofacial patter of this populations which should be properly compare for diagnostic and therapeutic measure. DOI: http://dx.doi.org/10.3329/updcj.v4i1.21163 Update Dent. Coll. j: 2014; 4 (1): 27-30